Thinking- Skins: Cyber-physical systems as foundation for intelligent adaptive façades - Böke, Jens (A+BE | Architecture and the Built Environment, 2020)
Under the guiding concept of a thinking skin, the research project examines the transferability of cyber-physical systems to the application field of façades. It thereby opens up potential increases in the performance of automated and adaptive façade systems and provides a conceptual framework for further research and development of intelligent building envelopes in the current age of digital transformation. The project is characterized by the influence of digital architectural design methods and the associated computational processing of information in the design process. The possible establishment of relationships and dependencies in an architecture understood as a system, in particular, are the starting point for the conducted investigation. With the available automation technologies, the possibility of movable building constructions, and existing computer-based control systems, the technical preconditions for the realisation of complex and active buildings exist today. Against this background, dynamic and responsive constructions that allow adaptations in the operation of the building are a current topic in architecture. In the application field of the building envelope, the need for such designs is evident, particularly with regards to the concrete field of adaptive façades. In its mediating role, the façade is confronted with the dynamic influences of the external microclimate of a building and the changing comfort demands of the indoor climate. The objective in the application of adaptive façades is to increase building efficiency by balancing dynamic influencing factors and requirements. Façade features are diverse and with the increasing integration of building services, both the scope of fulfilled façade functions and the complexity of today’s façades increase. One challenge is the coordination of adaptive functions to ensure effective reactions of the façade as a complete system. The ThinkingSkins research project identifies cyber-physical systems as a possible solution to this challenge. This involves the close integration of physical systems with their digital control. Important features are the decentralized organization of individual system constituents and their cooperation via an exchange of information. Developments in recent decades, such as the miniaturisation of computer technology and the availability of the Internet, have established the technical basis required for these developments. Cyber-physical systems are already employed in many fields of application. Examples are decentralized energy supply, or transportation systems with autonomous vehicles. The influence is particularly evident in the transformation of the industrial sector to Industry 4.0, where formerly mechatronic production plants are networked into intelligent technical systems with the aim of achieving higher and more flexible productivity. In the ThinkingSkins research project it is assumed that the implementation of cyber-physical systems based on the role model of cooperating production plants in IIndustry 4.0 can contribute to an increase in the performance of façades. Accordingly, the research work investigates a possible transfer of cyber-physical systems to the application field of building envelopes along the research question: How can cyber-physical systems be applied to façades, in order to enable coordinated adaptations of networked individual façade functions? To answer this question, four partial studies are carried out, which build upon each other. The first study is based on a literature review, in which the understanding and the state-of-the-art development of intelligent façade systems is examined in comparison to the exemplary field of application of cyber-physical systems in the manufacturing industry. In the following partial study, a second literature search identifies façade functions that can be considered as components of a cyber-physical façade due to their adaptive feasibility and their effect on the façade performance. For the evaluation of the adaptive capabilities, characteristics of their automated and adaptive implementation are assigned to the identified façade functions. The resulting superposition matrix serves as an organizational tool for the third investigation of the actual conditions in construction practice. In a multiple case study, realized façade projects in Germany are examined with regard to their degree of automation and adaptivity. The investigation includes interviews with experts involved in the projects as well as field studies on site. Finally, an experimental examination of the technical feasibility of cyber-physical façade systems is carried out through the development of a prototype. In the sense of an internet of façade functions, the automated adaptive façade functions ventilation, sun protection as well as heating and cooling are implemented in decentrally organized modules. They are connected to a digital twin and can exchange data with each other via a communication protocol. The research project shows that the application field of façades has not yet been exploited for the implementation of cyber-physical systems. With the automation technologies used in building practice, however, many technical preconditions for the development of cyber-physical façade systems already exist. Many features of such a system are successfully implemented within the study by the development of a prototype. The research project therefore comes to the conclusion that the application of cyber-physical systems to the façade is possible and offers a promising potential for the effective use of automation technologies. Due to the lack of artificial intelligence and machine learning strategies, the project does not achieve the goal of developing a façade in the sense of a true ThinkingSkin as the title indicates. A milestone is achieved by the close integration of the physical façade system with a decentralized and integrated control system. In this sense, the researched cyber-physical implementation of façades represents a conceptual framework for the realisation of corresponding systems in building practice, and a pioneer for further research of ThinkingSkins.